Prevention Model of Disguised Crime in Indonesian Banking Facing the Deviation Actions of The Credit Use/Side Streaming by Debtor; Theoretical Review On Risk Management Of Default Due To Side Streaming - Mas Ahmad Yani; Muhammad Mustofa (Jurnal Cita Hukum, 2019)
AbstractThe purpose of this paper is to explore and conduct systematical research through reading materials (researching by reading) on the possibility of prevention steps to prevent or reduce the Deviation Actions of the Credit Use (Side Streaming) by Debtor in the Problem of Banking Credit Facilities Utilization in Indonesia.  This paper is constructed by referring to one step of researching conducted by Ian Crow and Natasha Semmens in “Researching Criminology” (2006). It is stated that in researching by reading there are three approaches, they are (1) process of literature review; (2) process of reading and utilizing other people research findings; and (3) process of data analysis which is not used in researches, for example data taken from a writing in a newspaper or other mass media called content analysis. This research concludes that although the mode has been regulated in Law of Crime, the actions of side streaming have not been set up in banking crime actions in Indonesia. For the time being, side streaming occurs due to the availability of chances or opportunities and the possibility of using it to hide fraudulent misrepresentation actions.Keyword: Prevention, Side streaming, Criminal Banking AbstrakTujuan dari makalah ini adalah untuk mengeksplorasi dan melakukan penelitian sistematis melalui bahan bacaan tentang kemungkinan langkah-langkah pencegahan atau mengurangi tindakan penyimpangan Penggunaan Kredit (Side Streaming) oleh Debitur dalam Masalah pemanfaatan fasilitas kredit Perbankan di Indonesia. Makalah ini dibangun dengan mengacu pada satu langkah penelitian yang dilakukan oleh Ian Crow dan Natasha Semmens dalam "Researching Criminology" (2006). Dinyatakan bahwa dalam meneliti dengan membaca ada tiga pendekatan, yaitu (1) proses tinjauan literatur; (2) proses membaca dan memanfaatkan temuan penelitian orang lain; dan (3) proses analisis data yang tidak digunakan dalam penelitian, misalnya data yang diambil dari tulisan di koran atau media massa lainnya yang disebut analisis konten. Penelitian ini menyimpulkan bahwa meskipun modus kejahatan ini telah diatur dalam Hukum Pidana, namum tindakan side streaming belum diatur dalam tindakan kejahatan perbankan di Indonesia. Untuk saat ini, Side Streaming terjadi karena ketersediaan peluang dan kemungkinan menggunakannya untuk menyembunyikan tindakan keliru penipuan.Kata kunci: Pencegahan, Penyimpangan Penggunaan Kredit, Kejahatan Perbankan АннотацияЦелью данной статьи является изучение и проведение систематических исследований путем чтения печатного материала о возможности превентивных мер или сокращения девиантности по использованию кредита дебиторами в проблемах использования банковских кредитных средств в Индонезии. Эта статья была подготовлена в рамках одноэтапного исследования, проведенного Яном Кроу и Наташей Семменс в «Researching Criminology» (2006). Утверждается, что при исследовании посредством чтения существует три подхода, а именно: 1) процесс обзора литературы; 2) процесс чтения и использования результатов исследований других людей; и 3) процесс анализа данных, которые не используются в исследованиях, например, данных, взятых из записей в газетах или других средствах массовой информации, называемых контент-анализом. В результате этого исследования мы пришли к выводу, что, хотя этот способ преступления регулируется в Уголовном законе, однако side streaming не регулируется законом о банковских преступлениях в Индонезии. На данный момент side streaming происходит из-за наличия возможности использовать его для сокрытия мошеннических действий.Ключевые слова: предотвращение, девиантность по использованию кредита, банковские преступления